LA FUENTE AMARGA: UNA APROXIMACIÓN A LA ENTIDAD DEL BRONCE FINAL EN EL ENTORNO PRELITORAL DE MAZARRÓN (MURCIA) - Ros Sala, María Milagrosa (Anales de Prehistoria y Arqueología, 1987)
A series of ceramics from the site «La Fuente Amarga», in Mazarrón (Murcia, España), is studiet in this work. Due to the lack of an archeological register of these materials, it only allows a comparative analysis showing its possible cultural adscription to the Middle Late Bronze Age in the Southeast Spain.